2022
DOI: 10.3390/ma15134389
|View full text |Cite
|
Sign up to set email alerts
|

Cracking Resistance of Recycled Rubber Asphalt Binder Composed of Warm-Mix Additives

Abstract: Warm-mix asphalt technology has been applied to recycled rubber asphalt binder (RAB), which forms warm-mixed crumb rubber-modified asphalt binder (W-RAB) as a “green” material for environmental conservation and to enhance road performance. Furthermore, low-temperature cracking is one of the major distresses for asphalt pavement, which drastically restricts ride quality and service level. Therefore, the main objective of this study is to comparatively analyze the low-temperature properties of W-RABs based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Rubber asphalt has good high and low temperature performance and deformation resistance [ 11 , 12 ]. If it is used as a substitute for matrix asphalt, it will be beneficial for improving the performance of the gravel sealing layer [ 13 , 14 ]. In addition, the existing research has shown that adding fibers to the gravel sealing layer can effectively suppress the generation of reflective cracks on the road surface [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rubber asphalt has good high and low temperature performance and deformation resistance [ 11 , 12 ]. If it is used as a substitute for matrix asphalt, it will be beneficial for improving the performance of the gravel sealing layer [ 13 , 14 ]. In addition, the existing research has shown that adding fibers to the gravel sealing layer can effectively suppress the generation of reflective cracks on the road surface [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%